Late Triassic E-W striking shear zone and its implication on gold mineralization in the Xiaoqinling area, eastern China - Chen, Hong; Zhu, Gui-Fan; Bai, He; Cui, Guo-Shuai; Zhang, Huan-Huan; Mu, Pei-Ji; Jin, Yong-Jie (Frontiers in Earth Science, 2024)
The Xiaoqinling area is located in the eastern part of the Qinling Orogen and experiences early and late Mesozoic gold mineralization controlled by structural deformation.The relationship between the two stages of mineralization and the orogenic process of the Qinling Orogen is unclear. We investigated the deformation and alteration of E-W striking veins in the Xiaoqinling area. The geometric features revealed that all the veins developed within the E-Wstriking Guanyintang brittle-ductile shear zone. The vein was subparallel to the shear zone, dipped at 30°-60°, and had a wave-like appearance. The Guanyintang shear zone underwent three deformation stages: sinistral shearing (D1), dextral thrusting (D2), and sinistral normal faulting (D3). The development of ore-bearing quartz veins was controlled by deformation during D2, and the auriferous pyrite and minor chalcopyrite developed along the shear foliations. Re-Os dating of the molybdenite revealed a well-constrained isochron age of 230.2 ± 2.6 Ma, indicating the E-W striking shear zone developed in Late Triassic. This early Mesozoic shearing deformation in Xiaoqinling represents the early Mesozoic metallogenesis is correlated with the collisional orogeny of the Qinling orogen.